PERANCANGAN SISTEM INFORMASI IZIN CUTI KARYAWAN DENGAN MENGGUNAKAN FRAMEWORK Service Oriented Architecture (SOA) - fauzi yuni (Universitas Nusa Putra, 2021)
Niaga Nusa Abadi is a subsidiary of PT. Nojorono Tobacco International which has a parent in Kudus. The company, which has been operating for more than 80 years, is a distribution company of PT NTI and operates in supplying product needs to areas with 50 branches spread throughout Indonesia. The company has always been to build client trust by providing distribution services that are supported by a quality management system and reliable HR. The well-known products it distributes are Class Mild, Djinggo Minak, Aroma, Nikki Super, Niko International, Jazy Mild, Marathon and so on. Even though this company has been said to be large, but in the process of requesting leave employees still use a manual process that is able to hinder the process of requesting leave for employees. Implementation of